Cover Image. (24th August 2019) - Diabate, Seydou; Martin, Thibaud; Murungi, Lucy Kananu; Fiaboe, Komi K. M.; Subramanian, Sevgan; Wesonga, John; Deletre, Emilie
Abstract : The cover image is based on the ORIGINAL CONTRIBUTION Repellent activity of Cymbopogon citratus and Tagetes minuta and their specific volatiles against Megalurothrips sjostedti by Seydou Diabate et al., https://doi.org/10.1111/jen.12651 .